Carbon dioxide sequestration: influence of porous media on hydrate formation kinetics - Bhattacharjee, Gaurav; Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (ACS Sustainable Chemistry & Engineering, 2015)
In the present study, CO, sequestration by hydrate formation in porous sediments has been discussed. Two siliceous materials with high porosities, pumice and fire hardened red clay (FHRC), have been used as packing materials in a fixed bed setup to study hydrate formation kinetics. The results obtained using the aforementioned materials were compared with those obtained using silica sand and quartz. Carbon dioxide hydrate formation kinetics was studied at 3.0 MPa pressure and 274 K temperature. Two different types of experiments were conducted: (a) using a constant volume of water and (b) maintaining a constant bed height. These experiments were conducted using the different porous media individually as packing materials. It was observed that pumice as the porous medium showed better hydrate formation kinetics resulting in 46 mol % water to hydrate conversion in 5 h. Moreover, kinetics was enhanced with decrease in the bed height of pumice; this suggests that at field scale adaptation of CO, sequestration in geological formations, mass transfer limitations would be significant. The effects of particle size on hydrate formation kinetics were also investigated. It was observed that hydrate formation kinetics was enhanced with decrease in the particle size fraction.
Keywords: Bed height; Gas hydrate; gas uptake; Geological sequestration; Particle size

Effect of the amino acid L-histidine on methane hydrate growth kinetics - Bhattacharjee, Gaurav; Choudhary, Nilesh; Kumar, Asheesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Natural Gas Science and Engineering, 2016)
In the present study, the effect of a polar amino acid, L-histidine on methane hydrate growth kinetics has been investigated. Methane hydrate formation experiments were carried out in a stirred tank reactor setup at pressure and temperature conditions of 274.15 K and 5.0 MPa respectively. Two different concentrations (0.1 and 1 wt %) of L-histidine were studied. Hydrate growth through molecular dynamic (MD) simulation was also studied; pressure and temperature conditions for the simulations were set at 10.0 MPa and 270.0 K, while the concentration of L-histidine was kept fixed at 0.94 wt %. Hydrate formation runs using MD simulation were carried out with optimal concentration of methane in water. The presence of L-histidine in the system was found to significantly enhance methane hydrate growth kinetics as compared to pure water for both experimental and MD simulation runs. Final gas consumption with 1 wt % L-histidine was found to be comparable to that with 1 wt % SDS, the most commonly used additive for hydrate promotion studies. L-histidine is a benign additive which offers considerable enhancement in methane hydrate formation kinetics and can be utilized for various hydrate based technologies such as methane storage and transport. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Crystal growth; Gas hydrate; kinetics; Molecular dynamic simulation

Kinetic promotion of methane hydrate formation by combining anionic and silicone surfactants: scalability promise of methane storage due to prevention of foam formation - Bhattacharjee, Gaurav; Barmecha, Vivek; Kushwaha, Omkar S.; Kumar, Rajnish (Journal of Chemical Thermodynamics, 2018)
Methane storage in its solid hydrate form has recently come up as a rather attractive and low risk option for large scale storage of the gas owing to its mild storage conditions, high gas retention capacity and benign (non-explosive) character. However, it has its fair share of limitations with the slow rate of hydrate formation being one of the most prominent. The addition of surfactants like Sodium dodecyl sulfate (SDS) to the hydrate forming system significantly speeds up the process of methane hydrate formation but the large amount of foam generated by these surfactants during the process of hydrate formation and dissociation stands as a major roadblock towards the scaling up of the technology. In the current work, a small amount of a silicon based surfactant has been proposed to be used as antifoam in conjunction with an anionic surfactant SDS to eliminate the foam generation while at the same time promote the kinetics of methane hydrate formation. The idea is simple, cost effective and can be a potential game-changer in the quest to develop a commercially scalable hydrate based methane storage technology. (C) 2017 Elsevier Ltd.
Keywords: Antifoam; Gas hydrate; kinetics; Methane storage; scale-up; Silicone surfactant

Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel